Hazards - Manuel, Mark; McElroy, Barrie; Smith, Roger 1930- (Cambridge Univ. Press, 1997)
Discusses such natural hazards as famines, earthquakes, and biological disasters and examines ways of dealing with them.
Keywords: Natural disasters -- Juvenile literature; Natural disasters